Delayed neurochemical effects of prenatal exposure to MeHg in the cerebellum of developing rats. (1st March 2018) - Heimfarth, Luana; Delgado, Jeferson; Mingori, Moara Rodrigues; Moresco, Karla Suzana; Pureur, Regina Pessoa; Gelain, Daniel Pens; Moreira, José Cláudio Fonseca
Graphical abstract: Highlights: Cerebellum of young rats is targeted by prenatal MeHg exposure. Gestational exposure to MeHg disrupts redox homeostasis in the cerebellum. MeHg decreases GSK3β, ERK1/2 and JNK phosphorylation. MeHg increases PP2B, PKAα and phospho-c-Raf(Ser259) immunocontent. Abstract: Human fetuses and neonates are particularly vulnerable to methylmercury (MeHg)-induced brain damage and are sensitive even to low exposure levels. Previous work of our group evidence that prenatal exposure to MeHg causes cognitive and behavioral alterations and disrupt hippocampus signaling. The current study aimed to investigate the effect of gestational exposure of rats to MeHg at low doses (1 or 2 mg/kg) on parameters of redox imbalance and key signaling pathways in the cerebellum of their offspring. Pregnant females received MeHg (treated group) or 0.9% saline water (control group) by gavage in alternated days from gestational day 5 (GD5) until parturition and analyzes were proceed in the cerebellum of 30-day-old pups. We found increased lipid peroxidation and protein carbonylation levels as well as decreased SH content in pups prenatally exposed to 2 mg/kg MeHg. In addition, misregulated SOD/catalase activities supported imbalanced redox equilibrium. We found decreased GSK3β(Ser9) phosphorylation, suggesting activation of this enzyme and dephosphorylation/inhibition of ERK1/2 and JNK pathways. Increased PKAα catalytic subunit could be upstream of hyperphosphorylated c-Raf(Ser259) and downregulated MAPK pathway. In addition, we found raised levels of the Ca 2+ -dependent protein phosphatase 2 B (PP2B). We also found preserved immunohistochemical staining for both glial fibrillary acidic protein (GFAP) and NeuN in MeHg-exposed pups. Western blot analysis showed unaltered levels of BAX/BCL-XL, BAD/BCL-2 and active caspase 3. Together, these findings support absence of reactive astrocytes, neuronal damage and apoptotic cell death in the cerebellum of MeHg treated pups. The present study provides evidence that prenatal exposure to MeHg leads to later redox imbalance and disrupted signaling mechanisms in the cerebellum of 30-day-old pups potentially predisposing them to long-lasting neurological impairments in CNS.